2017
DOI: 10.1080/13811118.2017.1319312
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Non-Suicidal Self-Injury in the Laboratory

Abstract: The majority of non-suicidal self-injury (NSSI) research has used self- or clinician-rated measures of behavior which (a) are subject to reporting biases, or (b) have limited use in experimental designs that could illuminate causal relationships. Laboratory-based behavioral tasks have therefore been developed to assess NSSI-related behaviors more directly. We reviewed the behavioral methods that have been developed to assess NSSI tendencies or behaviors over the past 30 years. Several categories of laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 115 publications
(191 reference statements)
1
15
0
Order By: Relevance
“…Participants were asked to submerge their hand, up to their wrist, in a cooler containing a mixture of water and crushed ice maintained at 2 • C with a water circulator that prevents the water surrounding the participant's hand from warming. These procedures are consistent with previous studies that have used the CPT to measure pain tolerance in the context of suicide and self-injury (Franklin et al, 2011;Ammerman et al, 2017).…”
Section: Baseline and State Pain Experiencessupporting
confidence: 87%
“…Participants were asked to submerge their hand, up to their wrist, in a cooler containing a mixture of water and crushed ice maintained at 2 • C with a water circulator that prevents the water surrounding the participant's hand from warming. These procedures are consistent with previous studies that have used the CPT to measure pain tolerance in the context of suicide and self-injury (Franklin et al, 2011;Ammerman et al, 2017).…”
Section: Baseline and State Pain Experiencessupporting
confidence: 87%
“…Most studies used self-reported questionnaires to measure impulsivity. Aside from the various limitations of self-reported measures, including recall bias, impression management, and motivation, in evaluating impulsivity (29), selfreported measures mainly examine trait impulsivity. Although notable as an indicator of general risk, trait impulsivity, a fixed marker of risk by definition, cannot inform the causal risk factors for NSSI (30).…”
Section: Discussionmentioning
confidence: 99%
“…The accepted epochs of the EEG data for both absolute (uV2) and relative (%) power were smoothed using fast Fourier transforms and averaged in four frequency bands by NeuroGuide's spectral analysis system. After performing FFT, the spectral density was averaged into specific frequency ranges as follows: delta (1-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and low gamma (30-50 Hz) (19,20). The relative power of each channel was calculated by dividing each band power by the total power of the channel.…”
Section: Resting Qeeg Measuresmentioning
confidence: 99%
“…Studies on (neuro-) biological underpinnings used NSSI proxies in the laboratory and found that individuals with NSSI, as compared to healthy controls (HCs), showed decreased subjective arousal [ 14 ] and a decreased heart rate in response to painful stimulation [ 15 , 16 ]. Likewise, decreased amygdala activation through pain was observed in samples of BPD individuals with NSSI [as reviewed by [ 17 ]]. Finally, involvement of the endogenous opioid system (EOS) has repeatedly been discussed with regard to the development and maintenance of NSSI [ 18 ], mainly due to its role in the perception and regulation of social, emotional, and physical pain [ 18 ].…”
Section: Introductionmentioning
confidence: 99%